The effectiveness of digital board advertising along MRT railway lines in Kuala Lumpur: a conceptual study on motorist engagement - Isahak Merican, Farah Merican; Awang Besar, Nazirul Mubin; Nazrin, Nizar; Rosman, Muhammad Redza (Universiti Teknologi MARA, Perak, 2025)
Digital Out-of-Home (DOOH) advertising has rapidly emerged as a dominant medium in urban environments, particularly when integrated with public infrastructure such as Mass Rapid Transit (MRT) systems. In Kuala Lumpur, digital boards installed along MRT railway lines and stations are prominently visible to motorists navigating major roads and highways. These strategically positioned boards aim to capture the attention of thousands of drivers and passengers daily, offering brands unparalleled exposure in high-traffic corridors. This conceptual study explores the effectiveness of such advertising from the perspective of road users rather than commuters. Specifically, it investigates how visibility, message clarity, motion design, environmental distractions, and travel conditions influence brand recall, perception, and behavioral outcomes. The study emphasizes that motorists constitute a unique demographic whose fleeting attention span requires concise, visually engaging, and culturally resonant advertising strategies. A conceptual framework is proposed to guide future empirical research, addressing the cognitive, emotional, and contextual dynamics of driver engagement. By situating the analysis within Kuala Lumpur’s distinctive urban and infrastructural context, this paper contributes to both academic discourse and industry practice. It also highlights the importance of localized content, motion graphics, and cultural adaptation to enhance engagement and recall. Ultimately, this research provides theoretical grounding for future studies and practical insights for advertisers seeking to optimize DOOH strategies along MRT corridors.